PENERAPAN MODEL INFORMATION RETRIEVAL UNTUK PENCARIAN KONTEN PADA PERPUSTAKAAN DIGITAL (Jurnal Publikasi Teknik Informatika, 2022)
The growth of the library will not be separated from the progress of science and information technology. In this case the library is closely related to information technology and science. Each helping the other. Libraries have a great responsibility to improve the reading habits of their users. Therefore, this digital library has a very positive influence on users' reading motivation. A digital library is a library that uses a collection of books that are in digital format and can be accessed via computers and smartphones. The digital library has implemented a repository. Repository is a container for storing various documents or information. The use of a repository greatly facilitates digital library users in finding the information they need. In this study, the method used to search for content information uses (information retrieval), in processing the search using the N-Gram Algorithm and Cosine Similarity to measure the similarity between the documents sought. Using the above method can speed up the process of searching for content in digital libraries and to find the relevance between search results and keywords.